Access to Insulin Products in Pakistan: A National Scale Cross-Sectional Survey on Prices, Availability, and Affordability - Saeed, Amna; Lambojon, Krizzia; Saeed, Hamid; Saleem, Zikria; Anwer, Naveed; Aziz, Muhammad Majid; Ji, Wenjing; Liu, Wenchen; Chen, Chen; Yang, Caijun; Fang, Yu; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2022)
Background: Diabetes is among the top ten most prevalent diseases in Pakistan, suggesting that these patients may be the major drug consumers. Insulin was discovered a century ago, to treat diabetes, however, its access in several parts of the globe remains an issue. So, we evaluated insulin access in Pakistan. Methods: A nationwide cross-sectional survey was conducted to evaluate the access to insulins and some comparator medicines in eight cities of Pakistan using a modified WHO/HAI methodology. The survey included 80 medicines outlets i.e. 40 private pharmacies and 40 public hospitals. Data for every unique insulin product available in the Pakistani market was obtained, including five comparator medicines. Percentage availability, median unit prices (MUPs), and affordability (the number of days' wages (NDWs) required for a month's course by the lowest-paid unskilled government worker) of all products were calculated, including originator brands (OBs) and biosimilar (BS) products. Results: Of all insulin products surveyed, 87.5% were manufactured by foreign multinational companies (MNCs). None of the insulin products had ideal availability of 80% in any of the surveyed health facilities. In the public sector, none of the insulin products were available in more than 50% of the hospitals surveyed. In the public sector, the overall availability of human insulin was 70% . While in the private sector, the overall availability of human insulin was 90% and analogue insulin was 62.5%. The analogue insulin products were 72.8% costlier than the human insulin products. The median prices of BS insulin were 25.4% lower than the OB products, indicating that almost one-fourth of the cost could be saved by switching to BS human insulins from OB human insulins. All oral anti-diabetic medicines were found to be affordable. Whereas, none of the insulin was affordable. The NDWs for human and analogue insulins were 1.38 and 5.06. Conclusion: In Pakistan, insulin availability falls short of the WHO's benchmark of 80%. Insulin continues to be unaffordable in both the private and government sectors. To increase insulin access, the government should optimize insulin procurement at all levels, promote local production, enforce biosimilar prescribing, and provide financial subsidies for these products.